Asperger's syndrome in autistic children and their modes of learning through casual speech method - Ong, Jessica Hai Liaw; Dani, Noor Aina; Johari, Ahmad Zaidi (American-Eurasian Network for Scientific Information, 2013)
The objective of this study is to identify the Asperger's syndrome in autistic children by observing their behaviour, their extralinguistics factors and to develop the best teaching method in learning Malay language. The five children with autistic learning disabilities were observed. This case study used for five children whom have been endorsed by a medical officer and special education teachers as people with autism. They participated in the Special Education Programme for Integrated Learning Disabilities. In order to select appropriate teaching methods for autistic children, researchers implemented six methods of learning in the classroom. There are Common Method without Music, Common Method without Songs, Common Method without Drama, Casual Speech Method with Music, Casual Speech Method with Songs and Casual Speech Method with Drama. Observations showed that the most frequent behavioral symptom displayed by the children was reduced when this method was implemented. Casual Speech Method with Songs is the best method to reduce the Asperger syndrome of five subjects to the minimum in learning Malay language. The Casual Speech Method with Songs is the best method and be created in Teaching Module in learning Malay language. This module can be reviewed by Ministry of Education to be applied in Special Education Programme for Integrated Learning Disabilities in Learning Malay language. Based of their observed behavior the best method produced a strategic learning method that can enhance the communication skill of autistic children.